The role of music performance anxiety in musical training: four personal histories - Oscar Casanova; María Elena Riaño; Francisco Javier Zarza-Alzugaray; Santos Orejudo (Frontiers in Psychology)
Musical Performance Anxiety (MPA) is one of the major obstacles many musicians face in the course of their training and careers. Few studies have approached this construct using a qualitative methodology. To apply such an approach, we gathered testimonials of life histories from four musicians – two pianists, a violinist, and a cellist – through semi-structured interviews. With an average age of 25, they had all studied classical music for at least 10 years. We subjected the protocols of those interviews to a phase and categorization process based on Interpretative Phenomenological Analysis. The first years of training were those when our interviewees recalled experiencing the greatest enjoyment in music-making: positive elements included family support, ensemble playing, and initial encounters with non-classical repertoire and improvisation. However, as our interviewees progressed through their academic courses and improved in terms of mastery of their instrument, they began to experience situations of anxiety. Physical symptoms appeared, regularly associated with situations such as examinations and auditions in front of a jury. Two of four respondents decided to terminate their music training before entering university level. To deal with symptoms of anxiety, several approaches were pursued: visualization, cognitive analysis, and self-medication. However, to mitigate MPA, our informants generally recommend more rational strategies: a realistic focus on objectives coupled with reinforcement of self-esteem. Institutions of musical learning can help students cope with this disorder by encouraging musical creativity and selecting educators who apply empathetic teaching styles well-adapted to their pupils’ needs. In the future, this type of qualitative research can be expanded to a greater number of informants with more diverse characteristics. The qualitative approach will help us to better understand the MPA phenomenon.